2000
DOI: 10.1136/ip.6.3.189
|View full text |Cite
|
Sign up to set email alerts
|

Public opinion about guns in the home

Abstract: Objectives-(1) Determine the frequency of gun ownership, acquisition, and transfer; (2) assess gun storage practices; and (3) compare the views of firearm owning and non-owning adults regarding the protective value of keeping a gun in the home. Setting and methods-Over three diVerent time periods (1995, 1996, and 1999) stratified, random digit telephone surveys were conducted in a five county area of metropolitan Atlanta, Georgia. Five hundred adults (aged 21+ years) responded to each survey. Results-The propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…A study of suicides of young men aged between 15 and 24 years in Finland 1988-1995 revealed that 74% of all suicides by shooting were committed with a licensed hunting gun [25]. A telephone survey in Atlanta, USA, showed that although up to 40% of households reported gun ownership, a majority judged the presence of a gun at home as dangerous, as it might be involved in accidental shooting, suicide or family homicide [26].…”
Section: Discussionmentioning
confidence: 99%
“…A study of suicides of young men aged between 15 and 24 years in Finland 1988-1995 revealed that 74% of all suicides by shooting were committed with a licensed hunting gun [25]. A telephone survey in Atlanta, USA, showed that although up to 40% of households reported gun ownership, a majority judged the presence of a gun at home as dangerous, as it might be involved in accidental shooting, suicide or family homicide [26].…”
Section: Discussionmentioning
confidence: 99%
“…36 Unemployment, poverty, and the inverse of urbanization are ecologic characteristics that have been associated with higher rates of suicide in various studies. [37][38][39][40][41] …”
Section: Independent Variablesmentioning
confidence: 98%
“…Secondarily, we examined beliefs about defensive firearm use because of their relevance to attitudes about firearm storage practices. A primary reason for having firearms in the home, and for keeping them stored loaded and unlocked, is the belief that they can be used defensively in the event of a home invasion [8,9,21,42,43]. The increased time required to load or unlock a firearm can be considered counterproductive to effective defensive use.…”
Section: Introductionmentioning
confidence: 99%